Advanced Greenhouse Horticulture New Technologies and Cultivation Practices - Koukounaras, Athanasios (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Greenhouse horticulture is one of the most intensive agricultural systems, focusing on the production of high-value products. This book presents current research findings that cover a wide range of new technologies and novel agricultural practices, which are preconditions for successful production in a very competitive global environment.